Proceedings of the 19th Annual SIGdial Meeting on Discourse and Dialogue 2018
DOI: 10.18653/v1/w18-5030
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Self-Disclosure in Spoken Dialogue Systems

Abstract: Self-disclosure is a key social strategy employed in conversation to build relations and increase conversational depth. It has been heavily studied in psychology and linguistic literature, particularly for its ability to induce self-disclosure from the recipient, a phenomena known as reciprocity. However, we know little about how self-disclosure manifests in conversation with automated dialog systems, especially as any self-disclosure on the part of a dialog system is patently disingenuous. In this work, we ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
2
38
1
Order By: Relevance
“…Consistent with prior work on the linguistic markers of self-disclosure, the examples show how texts judged to be self-disclosing tend to be accompanied by more extensive use of (1) first-person pronouns (e.g., “I,” “me”), (2) references to family and friends, and (3) words that convey emotionality—particularly negative emotions (Houghton and Joinson 2012; Okdie 2011). The presence of these common linguistic markers forms the foundation of algorithms designed to automatically detect depth of disclosure in online texts (Bak, Kim, and Oh 2012; Balani and De Choudhury 2015; Ravichander and Black 2018; Wang, Burke, and Kraut 2016).…”
Section: Study 1: Depth Of Disclosure Across Devices On Twittermentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with prior work on the linguistic markers of self-disclosure, the examples show how texts judged to be self-disclosing tend to be accompanied by more extensive use of (1) first-person pronouns (e.g., “I,” “me”), (2) references to family and friends, and (3) words that convey emotionality—particularly negative emotions (Houghton and Joinson 2012; Okdie 2011). The presence of these common linguistic markers forms the foundation of algorithms designed to automatically detect depth of disclosure in online texts (Bak, Kim, and Oh 2012; Balani and De Choudhury 2015; Ravichander and Black 2018; Wang, Burke, and Kraut 2016).…”
Section: Study 1: Depth Of Disclosure Across Devices On Twittermentioning
confidence: 99%
“… 5 Exploratory analyses of other LIWC categories indicated that tweets written on smartphones (vs. PCs) also tended to use relatively more informal language (i.e., netspeak, nonfluencies, swear words). While a more informal writing style might also point to greater self-disclosure on smartphones, we focus on the four linguistic markers that have been validated in prior work (e.g., Ravichander and Black 2018). …”
mentioning
confidence: 99%
“…To address this issue, topic models are used to produce focused responses augmenting existing neural based approaches to CAs (Dziri et al 2018). Targeted responses employ self-disclosure as a strategic approach for building an engaging conversation (Ravichander and Black 2018). For SE detection, topic models (Bhakta and Harris 2015) and NLP of conversations (Sawa et al 2016) are leveraged.…”
Section: Related Workmentioning
confidence: 99%
“…In both settings, topic decisions occurring in the first 5 user turns are not used for evaluations. Static User Embeddings: Motivated by the findings that most user characteristics can be inferred from initial interactions (Ravichander and Black, 2018), we derive a static user embedding vector for a conversation using the first 5 user turns and apply it for predicting topic decisions afterwards. Dynamic User Embeddings: Alternatively, we build a user embedding vector for user turn t using all previous user turns.…”
Section: Topic Decision Classifiermentioning
confidence: 99%